Діагностичні критерії та ефективність застосування в комплексній терапії нутрицевтиків за гастроентеральної патології у собак в умовах зоокомплексу «Троїцький» міста Дніпро - Жулянова, С. Г.; Zhulyanova, S. G. (Дніпровський ДАЕУ, 2022)
Встановлено, що використання нутрицевтиків у комплексній терапії за лікування гастроентериту сприяє прискореному відновленню функцій шлункового-кишкового тракту тварин та профілактики розладів у подальшому. It is established that the use of nutraceuticals in complex therapy for the treatment of gastroenteritis contributes to the accelerated recovery of the gastrointestinal tract of animals and the prevention of disorders in the future.
Diagnostic criteria and effectiveness of complex therapy of nutraceuticals in gastroenterological pathology in dogs in the zoo complex" Troi'c'kyj "in Dnipro
Keywords: сучасна ветеринарна медицина; modern veterinary medicine; гастроентеральна патологія у собак; gastroenterological pathology in dogs; нутрицевтики при лікуванні собак; nutraceuticals in the treatment of dogs; діагностика гастроентериту; diagnosis of gastroenteritis; комплексна терапія; complex therapy